Bilateral non-syndromic dentigerous cyst - Rare case report and literature review - Kshitij Omprakash Bang; Shweta Ramashray Yadav; Ramakrishna Shenoi; Nilima Budhraja; Pranav Ingole (Elsevier, 2021)
Dentigerous cysts are common developmental odontogenic cysts of the jaw. They occur in an wide age group, having male predominance and related to an unerupted tooth. They are usually asymptomatic and thus grows to a larger size before they are diagnosed. Their occurrence is usually solitary. This case reports the existence of dentigerous cysts with unerupted mandibular third molars bilaterally. No feature of any syndrome was found in this case.